Strategi Internal Guru Pendidikan Agama Islam Fokus pada Pembentukan Moral Komunikasi Siswa - Halimah, Siti; Kholida, Ematul; Putri Fatimatuzzahro (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Formal educational institutions in Indonesia require spiritual learning in learning activities, just as Islamic religious education has an important role in shaping the character of students. This article was written using qualitative methods with literature study for data collection. The results of this article's research review are that the role of PAI teachers makes a huge contribution, apart from spiritual teaching and moral insight, Islamic Religious Education educators function as role models for students, and help them develop strong ethical, social and emotional values. This shows how important the role of Islamic Religious Education teachers is in turning students into ethical individuals. Different from educators in other fields, these teachers bear greater responsibilities, especially in forming Islamic character.